1995
DOI: 10.1016/0092-8674(95)90125-6
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin synthase 2 gene disruption causes severe renal pathology in the mouse

Abstract: The prostaglandin endoperoxide H synthase isoform 2, cyclooxygenase 2 (COX-2), is induced at high levels in migratory and other responding cells by pro-inflammatory stimuli. COX-2 is generally considered to be a mediator of inflammation. Its isoform, COX-1, is constitutively expressed in most tissues and is thought to mediate "housekeeping" functions. These two enzymes are therapeutic targets of the widely used nonsteroidal anti-inflammatory drugs (NSAIDs). To investigate further the different physiologic role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
659
0
9

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,030 publications
(693 citation statements)
references
References 44 publications
25
659
0
9
Order By: Relevance
“…Male COX-1 -/-, COX-1 +/+ , COX-2 -/-, COX-2 +/-, and COX-2 +/+ mice maintained on a C57Bl/6-129/Ola background for over 35 generations [35,41] were received at our animal facility at 6 weeks of age from a private NIEHS colony maintained by Taconic Farms (Germantown, NY) separately from their commercially available colony. In order to prevent the inclusion of strain or genetic background confounders between COX deficient and wild type mice, all of the mice used in this study were derived from a maintenance colony of COX-1 +/-or COX-2 +/-males and females, as previously described [35,41,64]. Specifically, all mice used in this study were progeny derived from heterozygous by heterozygous matings and therefore all contained the same strain and genetic background.…”
Section: Animal Housingmentioning
confidence: 99%
“…Male COX-1 -/-, COX-1 +/+ , COX-2 -/-, COX-2 +/-, and COX-2 +/+ mice maintained on a C57Bl/6-129/Ola background for over 35 generations [35,41] were received at our animal facility at 6 weeks of age from a private NIEHS colony maintained by Taconic Farms (Germantown, NY) separately from their commercially available colony. In order to prevent the inclusion of strain or genetic background confounders between COX deficient and wild type mice, all of the mice used in this study were derived from a maintenance colony of COX-1 +/-or COX-2 +/-males and females, as previously described [35,41,64]. Specifically, all mice used in this study were progeny derived from heterozygous by heterozygous matings and therefore all contained the same strain and genetic background.…”
Section: Animal Housingmentioning
confidence: 99%
“…Wild-type fibroblasts were derived from CBAxBL6 mice that were originally purchased from Jackson Laboratory (Bar Harbor, ME). Cox-I knockout (Cox-I -/-) [21] and Cox-2 knockout (Cox-2 -/-) [25] fibroblasts derived from mice were originally obtained from the breeding colony from the University of North Carolina. Fibroblast cell lines were derived as previously described [31].…”
Section: C0v I M Imentioning
confidence: 99%
“…However, studies have indicated that this image is more complex, and both constitutively expressed Cox2 and inducible Cox1 genes have been described somewhat depending on tissue (Breder et al 1995;Harris et al 2001). They also seem to be differentially regulated, and have shown to have different function in knock-out mice, whereas COX1 seems to have housekeeping function while COX-2, accounts for the elevated production of prostaglandins (Dinchuk et al 1995;Langenbach et al 1995;Morham et al 1995). In teleosts there are additional copies of cox2, probably due to genome duplication.…”
Section: Introductionmentioning
confidence: 99%